Pesquisa científica em saúde: as representações sociais de jornalistas do Interior do Estado de São Paulo - Marques, Vivian Guilherme (Universidade Federal de São Carlos, 2019)
The journalist can be seen as an opinion maker, who refers to providing access to information, with an important role on the dissemination of topics related to scientific research in Brazil. The general objective is to analyze the Social Representations of the scientific research in health of journalists from the State of São Paulo in the light of the field of Science, Technology and Society (CTS) and the Public Communication of Science, since the way in which they construct and share their representations of the research determines their attitude towards them and how they spread it in their journalistic materials. It is an exploratory research, of qualitative character and with theoretical-methodological reference based on the Theory of Social Representations. Interviews were conducted with a group of ten journalists, who held the position of editor in print and / or television news media, from four municipalities in the central region of the State of São Paulo, characterized by the important scientific production, in which public universities and federal institutes. The results showed a profile of these essays researched: formed by few journalists; not segmented by publishers; headed mainly by men; graduates in communication; with training in private education; which prioritize the news value of 'Proximity'; which emphasize health issues and have an essentialist and triumphalist view of science. The analysis of the data was based on the content analysis, systematized by the IRAMUTEQ software, forming five classes, subdivided into two main themes: A) Conceptions about research - which brings the conceptions of the interviewees about health research or research in general; about how is done (what it is), for whom is made (who benefits from it) and for what is done (for what it serves) scientific research; B) Communication of science - brings the theme of scientific divulgation, or more specifically, about the relationship between journalists and researchers; and about when the research is agenda or relevant issue to becoming a subject. The analysis of the results observed that, for these journalists, the social representation of scientific research in health permeates questions related to the classical view of science, confirmed by the beliefs about the authority of researchers, scientists and physicians; and also for the importance of science for healing and treatment of diseases. This view does not corroborate the precepts of the CTS movement that aims at a reflection on the traditional academy on Science & Technology, seeking to promote a new vision that considers essential for scientific work to be socially contextualized and the importance of the media for the dissemination of these research, being a link with society. The research brings notes to the understanding of how S&T needs to be presented to journalists better: such as the inclusion of CTS discipline in the curriculum; besides promoting a narrowing between press and university. Whereas, the researcher also has its preponderant role in this process by facilitating access to information; offer suggestions of agenda that meet the needs of the press; and to know the daily life of an essay.
Health Scientific Research: the social representations of journalists from the State of São Paulo
Keywords: Jornalismo científico; Representações sociais; Comunicação pública da ciência; Ciência, tecnologia e sociedade; Pesquisa científica em saúde; Scientific journalism; Social representations; Public communication of science; Science, technology and society; Health scientific research; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::JORNALISMO E EDITORACAO::JORNALISMO ESPECIALIZADO (COMUNITARIO, RURAL, EMPRESARIAL, CIENTIFICO)